Pengaruh Electronic Word Of Mouth (EWOM), Sosial Media Influencers, dan Shopping Lifestyle Terhadap Impulsive Buying Produk Sepatu Aerostreet (Studi Kasus Pada Konsumen Gen Z Kota Malang) - Susilo, Agung Budi; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research sought to explore and evaluate the influence of electronic word of mouth (eWOM), social media influencers, and the shopping habits of TikTok users on impulsive purchasing behaviour for Aerostreet shoe products among Generation Z consumers in Malang City. The research employed a quantitative approach, utilizing a Likert scale as the measurement instrument. The sample was selected using purposive sampling, consisting of 100 Gen Z respondents. Primary data was gathered through a questionnaire distributed via Google Forms. Data analysis included validity and reliability testing, classical assumption tests, multiple linear regression, hypothesis testing, and determination tests, conducted using SPSS 26 software. The findings reveal that eWOM, social media influencers, and shopping lifestyle each have a partial influence on impulsive buying behavior. Keywords : Electronic Word Of Mouth, Sosial Media Influencers, Shopping Lifestyle, Impulsive Buying.